Buccoadhesive Drug Delivery Systems: A Review - Ravi Bhalodia; Biswajit Basu; Kevin Garala; Bhavik Joshi; Kuldeep Mehta (International Journal of Pharma and Bio Sciences, 2010)
Delivery of the desired drug as buccoadhesive drug delivery systems has been subject of interest since last 3 decades. The various advantages associated with these systems made the buccal drug delivery as a novel route of drug administration. This review highlights the anatomy and nature of oral cavity, theories of mucoadhesion, classical and new generation mucoadhesive polymers, various types of mucoadhesive dosage forms and drugs which can be incorporated and various evaluation methods for the measurement of mucoadhesion potential.